Clinical characteristics of varicella-zoster virus central nervous system infection in 108 unimmunocompromised patients - Ci, Xiaojiao; Zhang, Jihong; Lu, Jie; Qi, Xinyang; Ma, Yifang; Liu, Weiguo; Shi, Jingping (Frontiers in Neurology, 2025)
BackgroundVaricella-zoster virus (VZV) central nervous system infection is typically observed in immunocompromised patients, and there is a lack of studies involving large samples of non-immunocompromised individuals. In this study, we retrospectively analyzed 108 non-immunocompromised patients diagnosed with VZV central nervous system infection.MethodsThis retrospective study was conducted in the Department of Neurology, Affiliated Nanjing Brain Hospital, Nanjing Medical University, China. Metagenomic next-generation sequencing (mNGS) of cerebrospinal fluid (CSF) revealed a positive result for VZV with a sequence number greater than 3, leading to a clinical diagnosis of VZV central nervous system infection. We analyzed the patients’ age, gender, clinical manifestations, blood routine, erythrocyte sedimentation rate (ESR), CSF examination, magnetic resonance imaging (MRI), electroencephalogram (EEG), and Activities of Daily Living (ADL) scale scores (Barthel Index) on the day of admission and 3 month post-discharge.ResultsThe study involved 108 patients, average age was 47.58 ± 2.91 years old (16 to 80), 33 were female (30.60%) and 75 were male (69.40%). Clinical manifestations were fever (63.9%), headache (88.9%), nausea (50%), vomiting (27.8%), fatigue (50%), dizziness (25.0%), herpes zoster (47.2%), chickenpox (0.9%), peripheral facial paralysis (19.4%), encephalopathy (5.6%), and myelitis (2.8%). The average white blood cell (WBC) count was 7.40 ± 0.48*109/l, the average CRP was 6.58 ± 0.69 mg/L, and the average ESR was 7.79 ± 0.53 mm/h. 28.1% of patients exhibited elevated lumbar puncture pressure, the average lumbar puncture pressure was 155.41 ± 2.38 mmH2O; the average CSF WBC count was 196.60 ± 3.98*10^6/l, the average CSF protein was 1.35 ± 0.03 g/L, the average CSF glucose was 3.41 ± 0.03 mmoL/L, the average CSF chloride was 116.62 ± 0.15 mmoL/L, the average CSF IgG index was 0.66 ± 0.01, the average mNGS examination of VZV sequence count was 626.25 ± 5402.17. Head MRI scans revealed no new lesions; three patients’ spinal cord MRI displayed short-segment, non-transverse, and non-continuous patchy long T1 and long T2 signals in the thoracic or cervical spinal cord. On the first day of admission, 41.7% of the patients achieved ADL score of 100 points, 19.4% scored between 41 and 99 points, and 38.9% of the patients scored less than 40 points. All patients received intravenous infusions of acyclovir with low-dose corticosteroids. An outpatient review conducted 3 months after discharge indicated 98.15% of the patients recovered well without any sequelae.ConclusionVZV encephalitis in immunocompetent individuals typically presents with mild clinical symptoms and has a favorable prognosis. VZV should be considered the common pathogen in the management of patients without immunocompeted condition with encephalitis.